Probing Hepatic Glucose Metabolism via 13C NMR Spectroscopy in Perfused Livers—Applications to Drug Development - Corin O. Miller (MDPI AG, 2021)
Despite being first published over 40 years ago, the combination of 13C nuclear magnetic resonance spectroscopy (NMR) and the isolated perfused liver preparation remains a unique and relevant approach in investigating the effects of pharmacological interventions on hepatic metabolism. The use of intact, perfused livers maintains many metabolic reactions at their respective rates in vivo, while the use of 13C-labelled substrates in combination with 13C NMR allows for a detailed study of specific pathways, as well as the design of robust assays which can be used to evaluate novel pharmacological agents. In this review article, we share some of the methods used to probe glucose metabolism, and highlight key findings and successes derived from the application of this specialized technique to the area of drug development for diabetes and related metabolic disorders.